2018
DOI: 10.3168/jds.2017-13461
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA quality in raw and reconstituted milk during sterilization

Abstract: Responses to milk sterilization are usually evaluated only in terms of physicochemical properties and microbial safety, thus undervaluing the importance of DNA quality in an authentication process by methods based on PCR. Because DNA is a heat-sensitive molecule, we hypothesized that the heating process may impair the detection or quantification of DNA in raw fresh milk (FM) or reconstituted milk (RM), and that differences in DNA quality might exist between FM and RM. We thus investigated the effects of steril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Compared with the positive control, all the extracted DNA samples showed serious smearing and the fragment length is between 100 bp and 2000 bp, which is shorter than the positive control, indicating that UHT treatment severely degraded the DNA in the milk. This result is similar to the previous report, which suggested that the DNA extracted from raw milk will gradually degrade into small fragments when the raw milk was treated by autoclaving from 0 min to 15 min (Liao et al, 2018a). In addition, there were no obvious differences in DNA degradation at different storage stages of UHT milk.…”
Section: Dna Integritysupporting
confidence: 91%
See 1 more Smart Citation
“…Compared with the positive control, all the extracted DNA samples showed serious smearing and the fragment length is between 100 bp and 2000 bp, which is shorter than the positive control, indicating that UHT treatment severely degraded the DNA in the milk. This result is similar to the previous report, which suggested that the DNA extracted from raw milk will gradually degrade into small fragments when the raw milk was treated by autoclaving from 0 min to 15 min (Liao et al, 2018a). In addition, there were no obvious differences in DNA degradation at different storage stages of UHT milk.…”
Section: Dna Integritysupporting
confidence: 91%
“…Mislabels and ingredient substitutions of food are major issues in the food industry (Cawthorn et al, 2013;Everstine et al, 2013;Wong & Hanner, 2008). To ensure food quality, the DNA-based method has been a reliable, accurate, and speedy tool to correct mislabeling (Liao et al, 2017a(Liao et al, , 2018a. However, the PCR-based method largely depends on the purity and intactness of DNA extracted from food (Spaniolas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H-13 C HMBC is useful to research the correlation between 13 C nuclear and 1 H nuclear. Through the correlation between 13 C and 1 H nuclear, substances identified by 1 H NMR spectra can be confirmed further. And the results showed that the qualitative result was reliable.…”
Section: Nmr Analysismentioning
confidence: 75%
“…been reported that the content of furosine is only affected both by heating temperature and also by storage time and conditions. 7,8 For example, the furosine and lactulose content is changed when the storage temperature reaches 30 ∘ C. 3 Some techniques have been developed to detect reconstituted milk, such as front-face fluorescence spectroscopy, 9 matrix-assisted laser desorption / ionization time of flight mass spectrometry (MALDI-TOF MS), 10 high-performance liquid chromatography (HPLC), 11,12 polymerase chain reaction (PCR), 13 and capillary zone electrophoresis with ultraviolet detection (CZE-UV). 14 However, sample pretreatments for these methods are complex and time consuming, so there is a need to develop a rapid, accurate, and simple method for the identification of reconstituted milk and UHT milk.…”
Section: Introductionmentioning
confidence: 99%
“…These treatments cause the degradation of DNA molecules (J. Liao, Yang, Sheppard, & Liu, 2018). In terms of purity and PCR inhibitors presence, lower purity of DNA was observed in heat-treated milk powder due to denatured proteins that can co-precipitate with genomic DNA, comparing with DNA purity obtained from raw milk (J Liao, Liu, Ku, et al, 2017).…”
Section: Dna Integrity and Food Processingmentioning
confidence: 99%